Gestión financiera y su incidencia en el capital de trabajo de las microempresas del sector servicio - Santillán Santillán, John Stalin (2021)
In this research work called Financial Management and its impact on the working capital of micro-enterprises in the service sector, the importance of an efficient administration of working capital is analyzed, as a strategic tool to achieve the operation of SMEs and their permanence in the time. Working capital is the minimum cash that companies need to normally cover their normal operations of the business line. Proper management provides the necessary liquidity to cover short-term obligations, as a result of the efficient application of a cash conversion cycle………